Intrahepatic levels of microbiome-derived hippurate associates with improved metabolic dysfunction-associated steatotic liver disease - Maxime Deslande; Francesc Puig-Castellvi; Inés Castro-Dionicio; Romina Pacheco-Tapia; Violeta Raverdy; Robert Caiazzo; Guillaume Lassailly; Audrey Leloire; Petros Andrikopoulos; Yasmina Kahoul; Nawel Zaïbi; Bénédicte Toussaint; et al. (Molecular Metabolism)
Objective: Metabolic dysfunction-associated steatotic liver disease (MASLD) is characterised by lipid accumulation in the liver and is often associated with obesity and type 2 diabetes. The gut microbiome recently emerged as a significant player in liver metabolism and health. Hippurate, a host-microbial co-metabolite has been associated with human gut microbial gene richness and with metabolic health. However, its role on liver metabolism and homeostasis is poorly understood. Methods: We characterised liver biospies from 318 patients with obesity using RNAseq and metabolomics in liver and plasma to derive associations among hepatic hippurate, hepatic gene expression and MASLD and phenotypes. To test a potential beneficial role for hippurate in hepatic insulin resistance, we profile the metabolome of (IHH) using ultra-high-performance liquid chromatography coupled to high-resolution tandem mass spectrometry (UHPLC-MS/MS), and characterised intracellular triglyceride accumulation and glucose internalisation after a 24 h insulin exposure. Results: We first report significant associations among MASLD traits, plasma and hepatic hippurate. Further analysis of the hepatic transcriptome shows that liver and plasma hippurate are inversely associated with MASLD, implicating lipid metabolism and regulation of inflammatory responses pathways. Hippurate treatment inhibits lipid accumulation and rescues insulin resistance induced by 24-hour chronic insulin in IHH. Hippurate also improves hepatocyte metabolic profiles by increasing the abundance of metabolites involved in energy homeostasis that are depleted by chronic insulin treatment while decreasing those involved in inflammation. Conclusions: Altogether, our results further highlight hippurate as a mechanistic marker of metabolic health, by its ability to improve metabolic homeostasis as a postbiotic candidate.